2023
DOI: 10.3390/fire6020060
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Fire Regimes and Associated Territorial Features in a Fire-Prone Mediterranean Region

Abstract: Fire regimes in Mediterranean countries have been shifting in recent decades, including changes in wildfire size and frequency. We sought to describe changes in fire regimes across two periods (1975–1995 and 1996–2018) in a fire-prone region of central Portugal, explore the relationships between these regimes and territorial features, and check whether these associations persisted across periods. Two independent indicators of fire regimes were determined at parish level: fire incidence and burn concentration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 81 publications
11
11
0
Order By: Relevance
“…However, it should be noted that much European forest, especially in the south, is currently man-made, sometimes including exotic species such as eucalypt rather than natural forests [59]. In Mediterranean climate regions such as the study area, the high prevalence of monocultural forest plantations in the landscape and its excessive spatial concentration substantially increase the risk of mega-wildfires [7,19] which, among many other negative impacts, are also responsible for releasing high amounts of organic carbon into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that much European forest, especially in the south, is currently man-made, sometimes including exotic species such as eucalypt rather than natural forests [59]. In Mediterranean climate regions such as the study area, the high prevalence of monocultural forest plantations in the landscape and its excessive spatial concentration substantially increase the risk of mega-wildfires [7,19] which, among many other negative impacts, are also responsible for releasing high amounts of organic carbon into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Fire regimes are used to depict combinations of fire frequency and severity [15,17,18]. Fire regimes are often characterized based on metrics such as total burn area, number of fire events, or spatiotemporal concentration indexes (e.g., Gini index), computed over a representative period of time [15,17,19]. Climate, topography, and LUC are acknowledged drivers of fire regimes [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Landscape specialization, in Portugal and other Mediterranean countries, is characterized by agricultural intensification on fertile lands and farmland retreat on marginal lands, where forests have regenerated or were installed, often with fast growing species in large patches, increasing fuel continuity and fire risks [6,10,21]. Nowadays, agricultural and forest plantations have created large scale specialized landscapes, while the rest of the territory is abandoned where no viable socioecological solution is possible [22].…”
mentioning
confidence: 99%
“…Actually, some studies point to a strong association of extreme wildfire events with some LULC types [3,[40][41][42][43], while others attributed LULC a minor influence on fire severity and size [44,45]. A wider region on central Portugal was recently studied focusing on landscape level (represented by parishes), and the authors found an expressive association of LULC with FRs, but even in these cases there was a limited number and range of landscape types [21,30,46]. In another recent study for all mainland Portugal assessing twelve FR drivers, the role of land-cover was variable, depending on FRs, but very influential in extremely hazardous regimes [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation